TEKNIK MPN COLIFORM SEBAGAI REFERENSI MATA KULIAH MIKROBIOLOGI - Sofiyana, Marinda Sari; Malahayati, Eva Nurul (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2018)
The aim of the research was to develop a research-based reference book using the coliform MPN technique.The development uses Hannafin development model which consists of three phases, they are (1) Need Assessment (Analysis of Needs); (2) Design (Design); (3) Develop and Implement (Development and Implementation. This development model is a product-oriented model. The first stage begins with needs analysis, product design, product manufacture, and product validation. The instruments used are questionnaires and interview guidelines. Data are analyzed descriptively. Based on the result of the analysis, it shows that the compiled references have met the eligibility requirements. The level of feasibility of the limited test of individual students is obtained at 80% with a valid category, the feasibility test from a media expert is obtained at 88.25% with a valid category, and the feasibility test for material content is 88.25% with a valid and feasible category to apply.